2022
DOI: 10.1080/20008198.2022.2027676
|View full text |Cite
|
Sign up to set email alerts
|

Rejection sensitivity and vulnerable attachment: associations with social support and PTSD symptoms in trauma survivors

Abstract: Background Although social support has been consistently associated with recovery from psychological trauma and prevention of posttraumatic stress disorder (PTSD), individual differences in seeking or benefitting from social support in trauma survivors are not well understood. Factors associated with negative internal working models of self and others, emotion dysregulation, and interrupted bonds with an individual’s social support groups such as vulnerable attachment and rejection sensitivity cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…Thus, future studies could examine these differences and potentially shed light on the neurobiological mechanisms through which different forms of maltreatment are related to rejection sensitivity. Future behavioral studies could also examine potential relevant moderating and mediating factors in the association between child maltreatment and rejection sensitivity, such as supportive relationships (Jittayuthd & Karl, 2022; McDonald et al, 2010) that may play a key role in attempts to break the intergenerational transmission of rejection sensitivity. From a gene–environment interaction perspective, future research exploring the influences of gene and environment on rejection sensitivity seems promising.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, future studies could examine these differences and potentially shed light on the neurobiological mechanisms through which different forms of maltreatment are related to rejection sensitivity. Future behavioral studies could also examine potential relevant moderating and mediating factors in the association between child maltreatment and rejection sensitivity, such as supportive relationships (Jittayuthd & Karl, 2022; McDonald et al, 2010) that may play a key role in attempts to break the intergenerational transmission of rejection sensitivity. From a gene–environment interaction perspective, future research exploring the influences of gene and environment on rejection sensitivity seems promising.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the research questions and hypotheses, as noted, this study aimed to investigate the prevalence of PTSD/CPTSD in this sample. In addition, we also examined the relationship between PTSD/CPTSD symptoms and interpersonal stress, dissociation and psychotic symptoms because these experiences are commonly associated with trauma ( 33 35 ).…”
Section: Methodsmentioning
confidence: 99%
“…The Eastasouth Journal of Social Science and Humanities (ESSSH)  networks, which provide individuals coping with trauma a sense of belonging, understanding, and assistance in practical matters3. Studies have shown that higher levels of perceived social support are associated with better mental health outcomes in PTSD patients [19], [20].…”
Section: Social Support Networkmentioning
confidence: 99%